Исследование возможностей резервного копирования веб-сайтов, созданных на основе WordPress - Егорова, Ирина Николаевна; Гладкая, Анна Алексеевна (НТУ "ХПИ", 2017)
В статье проведено исследование возможностей резервного копирования сайтов. Проведен анализ существующих плагинов. Предложен backup-плагин, разработанный на основе системы контроля версий GIT. Плагин позволяет осуществлять инкрементное и дифференциальное резервное копирование, восстанавливать backup из конкретной точки, а также автоматизировать процесс создания резервной копии посредством настройки расписания.

In order to simplify the process of creating and updating sites, content management systems (CMS) are used that provide the ability to jointly create, edit and publish content. One of the most popular CMS is WordPress. This article contains research details for backup possibilities of websites, developed in WordPress. Backup is the one of the essential components of site security. Backup is designed to restore data in case of loss or damage in the original location. Keeping only the development version is not sufficient, because the changes that are made to the site are often not reflected in its original version. Backing up sites involves creating a copy of the site's database or the site's file system. Backup should be performed regularly with frequency which is depending on the frequency of changes made to the site. To automate the backup process, special programs are used, as well as WordPress plugins that will allow to expand its capabilities.
Research for backup possibilities of websites created in WordPress
Keywords: плагины; облачные хранилища; система управления содержимым; дифференциальное резервное копирование; инкрементное резервное копирование; plugins; cloud services